STADY THE TECHNICAL AND ECONOMIC FEASIBILITY AND ENVIRONMENTAL IMPACT FOR A PROJECT OF RAISING MILK COWS IN GOGJALI REGION NINEVEH GOVERNORATE - Eman Younis Al Najjar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to determined by number of dairy cows breeding projects to produce milk using high productivity cows in Nineveh Governorate. The research aims to study the economic feasibility and environmental impact of the proposed project to be established in Nineveh Governorate using financial evaluation criteria. In order to prove the research hypothesis, the criteria of commercial profitability were used under the condition of certainty and uncertainty. It was found from the results of the research that the value of the net present value, the benefit-cost ratio, and the internal rate of return were 2911447, 1.74, and .18%, respectively. While the time period for recovering the project’s investment costs is 5 years and two months. The research concluded that the proposed project is economically acceptable, and that making the investment decision regarding its implementation does not accept hesitation even in the event of negative changes in the components of the evaluation model. By testing the sensitivity of the project to changes in its components, the negative effects of the project on the environment can be mitigated. Therefore, the research recommends financing the project because, the project does not involve environmental risks, the acceptable profits that it will achieve, and to encourage investment in establishing dairy cow breeding projects to contribute to limiting the import of fresh milk.